Haloperidol Versus Ondansetron for Prophylaxis of Postoperative Nausea and Vomiting - Rosow, Carl E.; Haspel, Kenneth L.; Smith, Sarah E.; Grecu, Loreta; Bittner, Edward A. (Anesthesia and analgesia, 2008)
Haloperidol is effective for postoperative nausea and vomiting prophylaxis, but there are almost no data comparing it to 5-HT(3) antagonists. Two hundred forty-four adults were randomized to receive i.v. haloperidol 1 mg or ondansetron 4 mg, during general anesthesia. Nausea, vomiting, need for rescue, sedation, extrapyramidal effects, QTc intervals, and time to postanesthesia care unit discharge were evaluated with a third-party blind design. There was no intergroup difference in any measure of efficacy or toxicity. Haloperidol and ondansetron subjects (78.2% and 76.8%) had complete response. Postoperatively, prolonged QTc occurred in 28.9% and 22.1% (N.S.). In a mixed surgical population, the efficacy and toxicity of postoperative nausea and vomiting prophylaxis with haloperidol 1 mg was not significantly different from ondansetron 4 mg.